Implementasi Semantic Computing pada Rumah Cerdas berdasarkan Perintah Pengguna menggunakan Smartphone - M Yusuf Effendi; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The application of IoT (Internet of Things) technology is widely applied, one of which is in smart homes. This sector is the most popular sector because its approach is close to human lifestyle, but in its application there are many difficulties, one of which is the difficulty for users to configure and integrate on each device. The semantic approach applied in this research can simplify the process of introducing IoT devices so that it can produce the ability to define, change, and produce better data readings. Based on the research conducted, the system was built using 2 sensors used as input data, namely the LDR (Light Dependent Resistor) sensor, the PIR sensor (Passive Infra red) and an output in the form of a relay actuator that can give a value of 1 (High) or 0 (Low ). This research is completed with a process unit that is a smartphone application that has the features of relation control, monitoring, and erasing devices connected to every data connected in firebase. The test results obtained performance with a delay of 0.999985350 seconds for the process of sending data from device to application and has a 100% percentage of the success of the system that is applied to the research implementation of semantic computing in smart homes based on user commands using a smartphone.